2012
DOI: 10.1071/rd12002
|View full text |Cite
|
Sign up to set email alerts
|

The effects of N-acetyl-L-cysteine supplementation on in vitro porcine oocyte maturation and subsequent fertilisation and embryonic development

Abstract: The effects of supplementation with 1.5 mM n-acetyl-l-cysteine (NAC) during in vitro oocyte maturation were studied. Oocytes were supplemented with 1.5 mM NAC during maturation for 0 to 24 h, 24 to 48 h, or 0 to 48 h then subjected to IVF and embryo development. Oocytes were evaluated after maturation for intracellular glutathione concentration, superoxide dismutase and glutathione peroxidase activities and DNA fragmentation. Fertilisation and embryonic development success were also evaluated. There was no eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…However, in all applied concentrations (0.1; 0.5 and 1.0 mM), SAC increased the % of cleaving zygotes following parthenogenetic activation. A similar effect has also been described in the case of cysteine, which in the study by the authors Li et al (2014) increased early embryo cleavage of porcine oocytes following ICSI, and also in the case of NAC, which improved the formation of male pronuclei and subsequent embryonic development (Whitaker, Casey & Taupier, 2012). On the basis of our results it is possible to conclude that SAC positively influences early embryo cleavage, a significant indicator of the quality of activated oocytes.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, in all applied concentrations (0.1; 0.5 and 1.0 mM), SAC increased the % of cleaving zygotes following parthenogenetic activation. A similar effect has also been described in the case of cysteine, which in the study by the authors Li et al (2014) increased early embryo cleavage of porcine oocytes following ICSI, and also in the case of NAC, which improved the formation of male pronuclei and subsequent embryonic development (Whitaker, Casey & Taupier, 2012). On the basis of our results it is possible to conclude that SAC positively influences early embryo cleavage, a significant indicator of the quality of activated oocytes.…”
Section: Discussionsupporting
confidence: 89%
“…Manuscript to be reviewed include the amino acid cysteine, which reduces levels of ROS in maturing bovine oocytes (Morado et al, 2003). A cysteine derivative, N-acetyl cysteine (NAC), positively influences the formation of pronuclei and the development of blastocytes in vitro in pigs (Whitaker, Casey & Taupier, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…N-acetyl cysteine (NAC), as a typical antioxidant with a thiol group and a precursor of cysteine, after being taken by the cell is used for GSH synthesis (Samuni, Goldstein, Dean, & Berk, 2013). Supplementing maturation medium with NAC had beneficial effect on developmental competence of the porcine oocytes (Whitaker, Casey, & Taupier, 2012). During the earliest stages of embryo development, up to the two-cell stage, glycine apparently functions as an organic osmolyte and is highly accumulated in the cell (Baltz & Tartia, 2010;Steeves & Baltz, 2005), which in turn can protect embryos against osmotic stress when they are cultured in hyperosmotic conditions (Dawson, Collins, & Baltz, 1998;Richards, Wang, Liu, & Baltz, 2010;Steeves et al, 2003).…”
mentioning
confidence: 99%
“…These researchers concluded that "GSH synthesized by intact cumulus cells during maturation culture improved oocyte maturation and played an important role in fertilization and embryonic development" (Maedomari et al, 2007). Many additional studies on supplementing porcine, bovine, macaque, and goat IVM medium with GSH or a GSH precursor exhibited positive effects on in vitro production of embryos (Zhou et al, 2008;Choe et al, 2010;Curnow et al, 2010;Lott et al, 2011;Nabenishi et al, 2011;Whitaker at al., 2012;Merton et al, 2013). However, one study in goats found that adding 1 mM GSH caused an increase in intracellular GSH in prepubertal goat oocytes but did not improve fertilization rates (Mayor et al, 2001).…”
Section: Previous Methods For Improving In Vitro Maturationmentioning
confidence: 99%